An unusual bilateral variation of musculocutaneous nerve. - Raju, S; Udaya Kumar, P; Ahmed Peer, S; Indira Devi, B (Department of Surgery, UKM Medical Centre, 2013)
Musculocutaneous nerve arises from the lateral cord (C5,6,7) of brachial plexus. Communications between the branches of brachial plexus are not so common. During routine dissection, we observed bilateral variation in 60-year-old female cadaver. In the present case, median nerve represented as a musculocutaneous nerve which supplied biceps brachii and brachialis, further continued into forearm as lateral cutaneous nerve of forearm on the right arm. This branch did not pass through coracobrachialis muscle but the coracobrachialis was innervated by a branch from lateral cord of brachial plexus. We also observed an abnormal communicating branch between the musculocutaneous and median nerve on left side of the arm. These kinds of variations are important for surgeons while performing surgeries of axilla and upperlimb.